Planning and the politicians : and other essays - Hanson, A. H. (New York : A. M. Kelley, 1969)
The collection of papers is on the purpose of parliament. It also presents unorthodox views on two special aspects of parliament's advisory and supervisory functions
Bibliographical references included in "Notes" (p. 321-339)
SJU
Loans
Keywords: Political science; Economic development; Great Britain